Isthmocele, an underecognised cause of secondary infertility and pregnancy outcome after endoscopic repair: a case report - Dawar, Aradhana K.; Nadkarni, Akshay K.; Sethi, Tuleeka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Isthmocele is a niche at the area of previous cesarean scar. 38 year old lady presented with secondary infertility and decreased ovarian reserve for IVF with previous caesarean 8 years back. Isthmocele confirmed on 3D USG. Hysteroscopic guided laparoscopic repair done after initial failed ET without surgery. Postsurgical observations were increased myometrial thickness, improvement of abnormal bleeding, pain and successful conception and delivery with frozen embryo transfer. Isthmocele is an iatrogenic pathology associated with obstetric and gynecological complications. It’s an under recognised cause of secondary infertility. Etiology could be poor tissue healing or surgical techniques favouring niche formation. It’s imperative to address to its causes during caesarean section to prevent it. Diagnosis is mostly missed. Given the absence of a clearly defined surgical method in literature, choosing the proper approach to treating isthmocele can be arduous. Laparoscopy provides a minimally invasive procedure in women with this defect with secondary infertility and improves the chances of conception.